2018
DOI: 10.22540/jfsf-03-008
|View full text |Cite
|
Sign up to set email alerts
|

Hip fractures in the elderly without osteoporosis

Abstract: In clinical practice, hip fracture is a very common reason for hospital admission in the elderly. Most subjects over the age of 65 years, experience an injury at the hip mostly after a fall. Many elderly persons suffer from osteoporosis, which is characterised by loss of bone mass and deterioration of bone microarchitecture thus increasing the susceptibility to fracture. Osteoporosis is defined by WHO as a Bone Mineral Density (BMD) of 2.5 standard deviations (SD) below that of a young adult as assessed by dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Although osteoporosis is prevalent in subjects with vertebral fracture and hip fracture, sarcopenia is another key point. People with sarcopenia have a 3-fold increased risk for a fall [ 22 ] and patients with TLCF also often develop sarcopenia, which is a condition characterized by loss of skeletal muscle mass and strength, along with physical dysfunction and a risk of death. Takahashi, K., et al reported that patients with TLCF have significantly decreased muscle mass, and the prevalence of sarcopenia in these patients is 22.7% to 43.7%, which is higher than the prevalence of other orthopedic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Although osteoporosis is prevalent in subjects with vertebral fracture and hip fracture, sarcopenia is another key point. People with sarcopenia have a 3-fold increased risk for a fall [ 22 ] and patients with TLCF also often develop sarcopenia, which is a condition characterized by loss of skeletal muscle mass and strength, along with physical dysfunction and a risk of death. Takahashi, K., et al reported that patients with TLCF have significantly decreased muscle mass, and the prevalence of sarcopenia in these patients is 22.7% to 43.7%, which is higher than the prevalence of other orthopedic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased bone density is a recognized risk factor for hip fractures. Within 50–80 years of age, the risk of hip fractures increase by 4 times due to the decreased bone density [ 2 ]. Senior hip fracture victims, who have comorbidities in the circulatory, respiratory, digestive, neurological, and urinary systems after staying in bed, will soon develop lung and urinary system infections, deep vein thrombosis in the lower extremities, bedsores, cardiovascular and cerebrovascular accidents, and multiple systemic organ failure.…”
Section: Introductionmentioning
confidence: 99%